Imaging of Kidney Cancer - Guermazi, Ali.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
This is one of the first books to deal specifically with diagnostic imaging of the entire spectrum of kidney cancers. Both new and conventional imaging modalities are fully considered. In an introductory chapter, the histopathological classification of kidney cancers is presented and discussed. The following five chapters describe in great detail the abilities, advantages, and disadvantages of the various imaging modalities used in the diagnosis of kidney cancers and the assessment of disease extension. Subsequent chapters offer an exhaustive description of the radiological features of the different histological subtypes of kidney cancer, with radiological and histological illustrations and tables. Interventional procedures employed in diagnosis, therapy, and treatment evaluation are described, with reference to the latest technical innovations. Finally, radiological and surgical advances in minimally invasive procedures for the treatment of kidney cancers are addressed. The book is well illustrated with carefully chosen and technically excellent images. Each of the 24 chapters is written by an internationally acclaimed expert, making this book the most current and complete treatment of the subject available. .
Histopathological Classification -- Ultrasound and Doppler in Kidney Cancer -- CT in Kidney Cancer -- Magnetic Resonance Imaging in Kidney Cancer -- Angiography in Kidney Cancer -- PET and PET/CT in Kidney Cancer -- Renal Cell Carcinoma -- Transitional Cell Carcinoma -- Kidney Sarcomas -- Cystic Renal Masses -- Collecting Duct Carcinoma -- Renal Sinus Neoplasms -- Small Renal Neoplasms -- Unusual Kidney Cancers -- Hereditary Renal Cancer -- Extraosseous Metastases and Local Recurrence -- Imaging of Bone Metastases -- Renal Lymphoma -- Lymphoproliferative Neoplasms -- Pediatric Kidney Cancer -- Percutaneous Biopsy and Radiofrequency Ablation -- Transarterial Embolization -- Preoperative Navigation of Nephron-Sparing Surgery -- Laparoscopic Partial Nephrectomy.
Keywords: Radiology; Oncology .; Urology; Radiotherapy; Imaging / Radiology; Diagnostic Radiology; Oncology; Urology; Radiotherapy